(untitled) (European Journal of Education and Psychology, 2011)
The purpose of the present study was to state how parents’ educational styles affect over the use of self-regulated learning strategies in a group of Secondary Education students and how mentioned strategies also influence on their academic performance. Four hundred and seventy eight Secondary Education students with ages between 12 and 16 took part in this investigation. In order to evaluate parents’ educational styles a set of values was made based on the instrument and the measuring of the self-regulated learning strategies was done through the Inventory of Learning Strategies and Study LASSI. Furthermore, students’ marks in three different subjects during the previous year were taken into consideration. The obtained results showed how those students whose parents are classified as democratic and permissive more often use self-regulated learning strategies when compared to children of authoritarian and negligent parents. Besides, it has been stated how this self-regulated learning positively influence over academic successful results.